Mediation of lateral hypothalamus orexin input to lateral habenula in the inhibitory effects of mechanical stimulation on psychomotor responses induced by cocaine - Jang, Han Byeol; Ahn, DanBi; Kim, Hyung Kyu; Guan, Xiaowei; Fan, Yu; Lee, Bae Hwan; Kim, Hee Young (Frontiers in Molecular Neuroscience, 2023)
Introduction The lateral hypothalamus (LH) plays an important physiological role in brain function and also plays an important role in substance abuse. The neuropeptides called orexin (or hypocretins) have been identified as being located exclusively in the cell bodies of the LH. Our previous studies have demonstrated that mechanical stimulation (MS) of the ulnar nerve produces strong inhibitory effects on cocaine addiction–like behaviors through activation of LH projection to the lateral habenula (LHb). Methods Therefore, the present study hypothesized that ulnar MS would suppress the psychomotor responses induced by cocaine through the orexinergic LH-to-LHb pathway. Results Ulnar MS attenuated cocaine enhancement of locomotor activity and 50-kHz ultrasonic vocalizations, which was prevented by antagonism of orexin-receptor type 2 (OX2R) in the LHb. Injection of orexin-A into the LHb reduced the cocaine-induced psychomotor responses. MS of the ulnar nerve excited LH orexinergic neurons. In addition, the excitation of LHb neurons by MS was blocked by the systemic administration of an OX2R antagonist. Discussion These findings suggest that MS applied to the ulnar nerve recruits an orexinergic LH-to-LHb pathway to suppress the psychomotor responses induced by cocaine.